Movie Comics : Page to Screen/Screen to Page - Davis, Blair, 1975- (Book collections on Project MUSE., 2017)
Movie Comics is the first book to study the long history of comics-to-film and film-to-comics adaptations, covering everything from silent films starring Happy Hooligan to sound films and serials featuring Dick Tracy and Superman to comic books starring John Wayne and Bob Hope. Blair Davis tracks the artistic coevolution of films and comics, investigates how the film and comics industries joined forces to expand the reach of their various brands, and contemplates our abiding desire to experience the same characters and stories in multiple forms.